SEXUAL HARASSMENT IN HIGHER EDUCATION INSTITUE: WOMEN AS LIYAN IN THE RELATIONALITY OF ARMADA RIYANTO - Angga, Stepanus; Kelen, Donatus Sermada (Universitas Tanjungpura, 2023)
This article aims to understand the problem of sexual violence that occurs tertiary institutions and its impact on victims, most of whom are women. Women have become liyan for immoral acts. Women have become objects of gratification for eyes and irregular minds. Women have also often been included in the inferior realm, which are seen as having no power, so they are vulnerable to being harassed. In general society, paradigms or stereotypes about women are still considered low. Women have become others who entered into oppression and adversity. This writing methodology was used as qualitative research by searching for data from journals, books, and online articles related to sexual violence and women as liyan. This article was based on Armada Riyanto's philosophy of relationality. Then the researcher interpreted and analyzed it into an actual critical study. This analysis produced findings about social awareness that the existential woman was not only her body but her entire self that was dignified and meaningful as a relational person.